Genetic Effects and Expression Patterns of the Nitrate Transporter (NRT) Gene Family in Populus tomentosa - Zhao, Lei; Chen, Panfei; Liu, Peng; Song, Yuepeng; Zhang, Deqiang (Frontiers in Plant Science, 2021)
Nitrate is an important source of nitrogen for poplar trees. The nitrate transporter (NRT) gene family is generally responsible for nitrate absorption and distribution. However, few analyses of the genetic effects and expression patterns of NRT family members have been conducted in woody plants. Here, using poplar as a model, we identified and characterized 98 members of the PtoNRT gene family. We calculated the phylogenetic and evolutionary relationships of the PtoNRT family and identified poplar-specific NRT genes and their expression patterns. To construct a core triple genetic network (association - gene expression - phenotype) for leaf nitrogen content, a candidate gene family association study, weighted gene co-expression network analysis (WGCNA), and mapping of expression quantitative trait nucleotides (eQTNs) were combined, using data from 435 unrelated Populus. tomentosa individuals. PtoNRT genes exhibited distinct expression patterns between twelve tissues, circadian rhythm points, and stress responses. The association study showed that genotype combinations of allelic variations of three PtoNRT genes had a strong effect on leaf nitrogen content. WGCNA produced two co-expression modules containing PtoNRT genes. We also found that four PtoNRT genes defined thousands of eQTL signals. WGCNA and eQTL provided comprehensive analysis of poplar nitrogen-related regulatory factors, including MYB17 and WRKY21. NRT genes were found to be regulated by five plant hormones, among which abscisic acid was the main regulator. Our study provides new insights into the NRT gene family in poplar and enables the exploitation of novel genetic factors to improve the nitrate use efficiency of trees.